Signifying the Effect of Relational and Experiential Cognitive Styles on Entrepreneurial Behavior: A Mediated Moderated Model - Aamir, Muhammad; Sarfraz, Muddassar; Khawaja, Kausar Fiaz; Usman, Habiba; Hu, Zhihua (Frontiers in Psychology, 2021)
This paper investigates the influence of rational and experiential cognitive styles on entrepreneurial behavior. Specifically, the moderating role of entrepreneurial intention and informal learning have been contemplated. Data has been accumulated from 320 undergraduate students of universities situated in Pakistan. Statistical Package for the Social Sciences (SPSS) and AMOS has been executed to examine the data and conduct statistical techniques. After confirming the validity and reliability of data and scale, results have signified that both cognitive styles significantly positively impact entrepreneurial behavior. Moreover, Informal learning moderates the relationship between entrepreneurial intention and cognitive styles (rational and experiential). Meanwhile, Entrepreneurial intention mediates the relationship between cognitive styles (rational and experiential) and entrepreneurial behavior emphatically.